Mites of the families Pygmephoridae and Neopygmephoridae (Acari:Pygmephoroidea) from soils in Mexico - Ignacio M. Vázquez-Rojas; Edith G. Estrada-Venegas; Mercedes G. López-Campos (Revista Mexicana de Biodiversidad)
Mites of the families Pygmephoridae and Neopygmephoridae have been poorly studied in Mexico. Previous records from this group are: Acinogaster (A.) kansensis from Chiapas, A. (A.) marianae from Veracruz, Pygmephorus americanus from Mexico, some species of Siteroptes fromPuebla and Pediculaster thailandensis from Quintana Roo. In this study we provide additional data, including specimens of Neopygmephoridae such as Kerdabania inconspicua, Bakerdania exigua, Pseudopygmephorus agarici, and P. shangaiensis; and of Pygmephoridae: Mahunkaniasecunda, Pediculaster ignotus and P. gracilis. Abundant specimens of Pediculaster ignotus were present in garlic crop soil.